2010
DOI: 10.1016/j.aquaculture.2009.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Stocking density and sex influence individual growth of Senegalese sole (Solea senegalensis)

Abstract: Growth is usually inversely correlated with stocking density of fish in culture. Senegalese sole aquaculture is affected by a high size variability and thus, this work tried to investigate the relationship of growth with density of two populations of 96 individually tagged Senegalese sole (318.7± 7.9 g; mean± standard error of the mean). Fish were reared at low (LD) and high (HD) density (60% and 180% of bottom coverage respectively) for 195 days. After 134 days (period 1), density conditions were exchanged be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 41 publications
(54 reference statements)
6
22
1
Order By: Relevance
“…The growth rate for larvae has been increased gradually with increasing temperature until 20 °C then decreased. These results agreed with most studies on biological development and temperature in Senegal sole as many authors have used a constant temperature of 20 ºC (Martinez et al, 1999;Parra and Yufera, 1999;Ribeiro et al, 1999;Yufera et al, 1999;Canavate et al, 2006;Sanchez et al, 2010;Salas-Leiton et al, 2011, 2012. The Senegal sole (Solea senegalensis) is a flatfish adapted to temperate waters of around 20-21 ºC (Drake et al, 1984).…”
Section: Effect Of Temperaturesupporting
confidence: 80%
“…The growth rate for larvae has been increased gradually with increasing temperature until 20 °C then decreased. These results agreed with most studies on biological development and temperature in Senegal sole as many authors have used a constant temperature of 20 ºC (Martinez et al, 1999;Parra and Yufera, 1999;Ribeiro et al, 1999;Yufera et al, 1999;Canavate et al, 2006;Sanchez et al, 2010;Salas-Leiton et al, 2011, 2012. The Senegal sole (Solea senegalensis) is a flatfish adapted to temperate waters of around 20-21 ºC (Drake et al, 1984).…”
Section: Effect Of Temperaturesupporting
confidence: 80%
“…Moreover, growth rate is probably one of the most well studied physiological parameters related to aquaculture, although other variables related to stress and endocrine systems have been studied in different species of interest for aquaculture, as in S. aurata (Caruso et al, 2005;Montero et al, 1999), S. senegalensis (Ambrosio et al, 2008;Salas-Leiton et al, 2008;Sánchez et al, 2010), D. labrax (Lupatsch et al, 2010) or Salmo salar (Hosfeld et al, 2009). Aquaculture activity requires the optimization of stocking densities along the life cycle of the species of interest in order to avoid the activation of the stress system and the consequent economic losses (Barton, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Because the sexes are often subject to different selective pressures regarding the tradeoff between growth and reproduction, the consequences of changes in resource abundance associated with changes in population density should be different for males and females (LeBlanc et al 2001). Accordingly, differential effects of population density variations on the growth of males and females have been reported for many taxa including fish (Isaac 2005, Sánchez et al 2010), but also minor effects of density on dimorphism have been reported (Garel et al 2006). In our experiments, perch females and males showed similar response to fish density variations.…”
Section: Discussionmentioning
confidence: 99%
“…The female–male growth differences in the study lakes were tested with analysis of variance for repeated measurements. This method can be used in growth studies including several back‐calculated and temporally autocorrelated measurements from the same individuals (Horppila and Nyberg 1999, Sánchez et al 2010). Additionally, the female–male difference in the average annual length increment was calculated for each lake for age group 1–6 and plotted against the water colour of the lakes.…”
Section: Methodsmentioning
confidence: 99%